1985
DOI: 10.1177/33.6.3158698
|View full text |Cite
|
Sign up to set email alerts
|

Localization of immunoreactive synthetic atrial natriuretic factor (ANF) in the heart of various animal species.

Abstract: The localization of two synthetic fragments of the C-ter-'Supported by a Medical Research Council ofCanada Group Grant to the Multidisciplinary Research Group on Hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
1
2

Year Published

1986
1986
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 201 publications
(72 citation statements)
references
References 0 publications
6
63
1
2
Order By: Relevance
“…Even though LAA is thought to play a central role in MR-proANP release, [7,8] studies using immunohistochemically techniques have demonstrated a greater number of intensely granulated cardiomyocytes secreting MR-proANP in the right rather than in the left atrium [9]. If the myocytes outside the LAA produce most of the MR-proANP, it can be difficult to measure the impact of LAA closure on MR-proANP levels, thereby explaining our results.…”
Section: Resultscontrasting
confidence: 49%
See 3 more Smart Citations
“…Even though LAA is thought to play a central role in MR-proANP release, [7,8] studies using immunohistochemically techniques have demonstrated a greater number of intensely granulated cardiomyocytes secreting MR-proANP in the right rather than in the left atrium [9]. If the myocytes outside the LAA produce most of the MR-proANP, it can be difficult to measure the impact of LAA closure on MR-proANP levels, thereby explaining our results.…”
Section: Resultscontrasting
confidence: 49%
“…It is important to notice that the right atrial appendage in our cohort has been left untreated, furthermore supporting that the right atrial appendage is an area of importance involved in ANP production. Studies using immunohistochemically techniques have also demonstrated a greater number of intensely granulated cardiomyocytes secreting MR-proANP in the right rather than in the left atrium [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These afferent signals play a role in fluid haemostasis and control of heart rate in response to changes in LA pressure. In support of this, one study demonstrated that 30% of all cardiac atrial natriuretic peptide (ANP) was found within the LAA [9]. Furthermore in the healthy human heart, ANP concentration in the LAA is present in 40-times the concentration of the rest of the LA [10].…”
Section: Laa Physiologymentioning
confidence: 59%